2023
DOI: 10.1126/sciadv.ade6675
|View full text |Cite
|
Sign up to set email alerts
|

The BAF complex inhibitor pyrimethamine reverses HIV-1 latency in people with HIV-1 on antiretroviral therapy

Abstract: Reactivation of the latent HIV-1 reservoir is a first step toward triggering reservoir decay. Here, we investigated the impact of the BAF complex inhibitor pyrimethamine on the reservoir of people living with HIV-1 (PLWH). Twenty-eight PLWH on suppressive antiretroviral therapy were randomized (1:1:1:1 ratio) to receive pyrimethamine, valproic acid, both, or no intervention for 14 days. The primary end point was change in cell-associated unspliced (CA US) HIV-1 RNA at days 0 and 14. We observed a rapid, modest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 72 publications
(153 reference statements)
0
11
0
Order By: Relevance
“…LRAs were combined with other therapies in six studies (vorinostat with maraviroc, vorinostat with tamoxifen, pyrimethamine with valproic acid, vorinostat with disulfiram, IL-7 with maraviroc, and nivolumab with ipilimumab). 27 , 39 , 42 , 52 , 55 , 56 Increase in CA US HIV-1 RNA was observed in all combinations except IL-7 with maraviroc, but none exhibited synergy between LRAs.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…LRAs were combined with other therapies in six studies (vorinostat with maraviroc, vorinostat with tamoxifen, pyrimethamine with valproic acid, vorinostat with disulfiram, IL-7 with maraviroc, and nivolumab with ipilimumab). 27 , 39 , 42 , 52 , 55 , 56 Increase in CA US HIV-1 RNA was observed in all combinations except IL-7 with maraviroc, but none exhibited synergy between LRAs.…”
Section: Resultsmentioning
confidence: 94%
“…Significant increases from baseline CA US HIV-1 RNA were found in all HDACis except for valproic acid monotherapy. 39 Of the eleven studies with transcription activators, CA US HIV-1 RNA increases were found in five studies, 34 , 41 , 44 , 48 , 49 with maraviroc 48 and disulfiram 41 having the best evidence for their effect. Furthermore, all four immune checkpoint inhibitors 54 , 55 , 56 , 57 and two vaccine studies 59 , 60 demonstrated CA US HIV-1 RNA increases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…48 hours after transfection, cells were collected and lysed in TRI reagent (Sigma) and total RNA was isolated as described before. 58 We then DNAse treated the RNA and synthetized cDNA using, respectively, DNAse I amplification grade kit (Invitrogen) and SuperScript II reverse transcriptase (Invitrogen) following the provided protocols.…”
Section: Methodsmentioning
confidence: 99%
“…To analyse the change in US and CS vRNA we performed a nested qPCR assay targeting Gag (US vRNA) and Tat-Rev (CS vRNA) as described before 58 , 59 with minor modifications. Briefly, for pre-amplification of US and CS vRNA 10 μL of diluted cDNA were used in a final volume of 25 μL using Platinum™ Taq DNA polymerase kit (Invitrogen) and nested US forward and reverse 1 primers for US vRNA detection or nested CS forward and reverse primers for CS vRNA detection ( Table 2 ).…”
Section: Methodsmentioning
confidence: 99%